Sustainability through open innovation : Carlsberg and the Green Fiber Bottle - Chesbrough, Henry, (SAGE Knowledge. Cases., 2018)
The case follows Danish brewer Carlsberg as it develops the Green Fiber Bottle, a beer bottle made of wood pulp, in collaboration with a startup, a small-to-medium sized enterprise (SME), and a Danish university. Sustainability was the primary motivator for the project, and open innovation was the primary development method. The case has a dual focus. First, it demonstrates how a company can successfully innovate by leveraging the concept of open innovation. Second, it shows how sustainability--and relatedly, the idea of purpose--can be a powerful motivator to drive open innovation efforts.